South-South relations and global environmental governance : Brazilian international development cooperation - Hochstetler, Kathryn (2019)
South-South relations have become increasingly relevant for understanding global environmental governance in the 21st century. This article explores the socio-environmental contributions and impacts of Brazilian South-South cooperation for international development. Case studies of its international technical cooperation and the international project finance of BNDES show a mixed picture, with environmental benefits countered by environmental harms.